Glucagon-Like Peptide-1 (GLP-1) during Ramadan: Narrative Review of the Published Literature - Khalid Mohammed Alayed (Hindawi Limited, 2023)
Ramadan fasting, a religious practice observed by Muslims worldwide, involves abstaining from eating, drinking, smoking, and using oral medications from dawn to dusk during the ninth lunar month. Studies have demonstrated that fasting during Ramadan has been shown to increase HDL cholesterol, leptin, adiponectin, and insulin sensitivity, as well as lower several hemostatic risk factors for cardiovascular diseases. Additionally, it may result in a drop in blood sugar levels, especially in diabetics who are also on blood sugar-lowering medicine. Hypoglycemia, characterized by low blood sugar levels, could also result from fasting during Ramadan. The GLP-1 (glucagon-like peptide-1) hormone plays a significant role in regulating glucose metabolism and insulin secretion, and Ramadan fasting can affect its production and release in the gut. Research contributes to our understanding of the utilization of GL-1 medications during Ramadan among patients, broadening therapy alternatives and offering insightful information for well-informed decision-making. Therefore, this narrative review aims to explore the current evidence that studies the safety and efficacy of GLP-1 agonists during Ramadan for nondiabetic and diabetic patients to ensure healthy fasting during Ramadan.